Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.leu.2401467
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor independence and BCR/ABL transformation: promise and pitfalls of murine model systems and assays

Abstract: The expression of the BCR-ABL fusion oncoprotein in primitive hematopoietic cells results in chronic myeloid leukemia. Over the past decade studies of several in vitro and in vivo cell systems revealed multiple signal transduction pathways activated by BCR-ABL. However, the precise function of BCR-ABL in the pathogenesis of CML is still unclear. The goal of this review is to synthesize data on intracellular signaling in the context of the diverse murine assay systems employed. We emphasize the importance of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…In contrast, we found that inhibition of Bcr/Abl inhibited CKIIa activity. These disparate results are difficult to compare because very different experimental conditions were used: at least in other systems, outcome of growth factor independence and transformation studies by Bcr/Abl have been shown to be cell-type-and assay-dependent (Ghaffari et al, 1999). Similar to our study, others have also found a transformation-stimulatory cooperation between CKIIa and other oncogenes.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, we found that inhibition of Bcr/Abl inhibited CKIIa activity. These disparate results are difficult to compare because very different experimental conditions were used: at least in other systems, outcome of growth factor independence and transformation studies by Bcr/Abl have been shown to be cell-type-and assay-dependent (Ghaffari et al, 1999). Similar to our study, others have also found a transformation-stimulatory cooperation between CKIIa and other oncogenes.…”
Section: Discussionsupporting
confidence: 57%
“…This hypothesis remains to be proven, although the existence of a rapamycin-resistant kinase, which contributes to phosphorylation of 4E-BP1, is suggested by the work of others using a dominantnegative form of mTOR (Edinger et al, 2003). Our data also demonstrate that yet another common target of cytokine-and Bcr-Abl-mediated signaling is 4E-BP1 (Figures 1c and 3c), and is in line with the prevailing understanding that Bcr-Abl-containing malignancies 'co-opt' existing cytokine-mediated signaling pathways to gain a proliferative/survival advantage over their normal counterparts (Ghaffari et al, 1999;Deininger et al, 2000). In primary CML cells, we observed that the effect of imatinib on inhibiting 4E-BP1 phosphorylation and induction of eIF4F was less dramatic than in Ba/ F3-Bcr-Abl and K562 cells, although combined inhibition of Bcr-Abl and mTORC1 was still required for maximal inhibition of 4E-BP1 phosphorylation, eIF4F formation and cyclin D3 protein expression (Figures 1d, 4 and 5f).…”
supporting
confidence: 89%
“…The existence of unknown genetic abnormalities in established cell lines might also obscure the function of the gene studied. Inconsistent results have been obtained from cell line studies in assessing the role of certain functional domains or motifs, such as the GRB2 SH2-binding site at Y177 of BCR and of the SH2 domain of ABL, in transformation by BCR-ABL (Ghaffari et al, 1999). Deletion of the SH3 domain of ABL results in a mutant form of the protein with increased tyrosine kinase activity, and expression of this truncated protein can transform both fibroblast and haematopoietic cell lines in vitro.…”
Section: Bcr-abl Domain Functions and CML Mouse Modelmentioning
confidence: 99%